Newborn screening and disease variants predict neurological outcome in isovaleric aciduria - Muetze, Ulrike; Henze, Lucy; Gleich, Florian; Lindner, Martin; Gruenert, Sarah C.; Spiekerkoetter, Ute; Santer, Rene; Blessing, Holger; Thimm, Eva; Ensenauer, Regina; Weigel, Johannes; Beblo, Skadi; et al. (Journal of Inherited Metabolic Disease, 2021)
Isovaleric aciduria (IVA), a metabolic disease with severe (classic IVA) or attenuated phenotype (mild IVA), is included in newborn screening (NBS) programs worldwide. The long-term clinical benefit of screened individuals, however, is still rarely investigated. A national, prospective, observational, multi-center study of individuals with confirmed IVA identified by NBS between 1998 and 2018 was conducted. Long-term clinical outcomes of 94 individuals with IVA were evaluated, representing 73.4% (for classic IVA: 92.3%) of the German NBS cohort. In classic IVA (N = 24), NBS prevented untimely death except in one individual with lethal neonatal sepsis (3.8%) but did not completely prevent single (N = 10) or recurrent (N = 7) metabolic decompensations, 13 of them occurring already neonatally. IQ (mean ± SD, 90.7 ± 10.1) was mostly normal but below the reference population (P =.0022) and was even lower in individuals with severe neonatal decompensations (IQ 78.8 ± 7.1) compared to those without crises (IQ 94.7 ± 7.5; P =.01). Similar results were obtained for school placement. In contrast, individuals with mild IVA had excellent neurocognitive outcomes (IQ 105.5 ± 15.8; normal school placement) and a benign disease course (no metabolic decompensation, normal hospitalization rate), which did not appear to be impacted by metabolic maintenance therapy. In conclusion, NBS reduces mortality in classic IVA, but does not reliably protect against severe neonatal metabolic decompensations, crucial for favorable neurocognitive outcome. In contrast, individuals with mild IVA had excellent clinical outcomes regardless of metabolic maintenance therapy, questioning their benefit from NBS. Harmonized stratified therapeutic concepts are urgently needed.
CRIS-Team Scopus Importer:2021-03-05
Keywords: isovaleric acidemia; isovaleric aciduria; long-term outcome; neonatal screening; newborn screening